2016
DOI: 10.1017/s1479262116000186
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distinctiveness of safflower cultivars of India and Mexico as revealed by SSR markers

Abstract: Safflower is a traditional oilseed crop in the world. Its seed oil is a healthy edible oil containing high amount of unsaturated fatty acids. Genetically diverse exotic cultivars are valuable germplasm for introducing new diversity in safflower improvement programmes. In this study, we characterized safflower cultivars of India (30) and Mexico (23) comprising varieties, hybrids and advanced lines developed over 50 years for genetic distinctiveness using 38 simple sequence repeat (SSR) loci. Genetic diversity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Molecular markers are considered important tools for the identification of cultivars, for allowing polymorphism analysis directly in the DNA [ 8 , 9 ]. In this respect, microsatellite or SSR markers have being extremely useful for cultivar distinction, particularly in the case of species with a narrow genetic base, where DNA fingerprinting may be highly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers are considered important tools for the identification of cultivars, for allowing polymorphism analysis directly in the DNA [ 8 , 9 ]. In this respect, microsatellite or SSR markers have being extremely useful for cultivar distinction, particularly in the case of species with a narrow genetic base, where DNA fingerprinting may be highly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kiran et al (2017) used 44 SSR markers for genetic diversity evaluation, linkage disequilibrium and population structure analysis among 148 accessions of safflower. Moreover, assessment of genetic distinctiveness among Indian and Mexican cultivars of safflower (Kadirvel et al, 2017), and association mapping of agronomic traits (Ambreen et al, 2018) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…These maps have used only a small number of marker loci and high‐density SSR linkage maps that are not yet available. Polymorphism in the set of reported SSR markers has been found to be low in safflower (Kadirvel et al., 2017; Usha Kiran et al., 2017), which is a limitation for QTL mapping in a specific mapping population. Recently, next‐generation sequencing (NGS) technologies and bioinformatics tools have become very helpful in extracting more marker loci across genomes (Bowers et al., 2016; Xia et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism in the set of reported SSR markers has been found to be low in safflower (Kadirvel et al, 2017;Usha Kiran et al, 2017), which is a limitation for QTL mapping in a specific mapping population.…”
mentioning
confidence: 99%